Functional assessment of tyrosinase variants identified in individuals with albinism is essential for unequivocal determination of genotype‐to‐phenotype correlation. (11th November 2016) - Mondal, M.; Sengupta, M.; Ray, K.
Summary: Background: Oculocutaneous albinism type 1 (OCA1), caused by pathogenic variations in the tyrosinase gene ( TYR ), is the most frequent and severe form of hypopigmentary disorder worldwide. While OCA1A manifests as a complete loss of melanin pigment, patients with OCA1B show residual pigmentation of the skin, hair and eyes. Limited experimental evidence suggests retention of TYR in the endoplasmic reticulum (ER) causes OCA1 pathogenesis. However, a comprehensive functional analysis of TYR missense variations and correlation with genotype is lacking. Objectives: Functional characterization of nonsynonymous tyrosinase variants in patients with OCA1 reported in the Albinism Database, dbSNP and the published literature, and an attempt to correlate them with reported and predicted phenotypes. Methods: Thirty‐four reported missense variants of TYR were subcloned by site‐directed mutagenesis, and the dual‐enzyme activities of the variant proteins were compared with the wild‐type. The degree of ER retention was also checked for each of the variants through endoglycosidase H (Endo H) digestion followed by immunoprecipitation and densitometric analysis. Results: Functional studies revealed one reported OCA1A variation with nearly 100% enzyme activity, 10 OCA1B variants lacking any enzyme activity, eight nonsynonymous single‐nucleotide polymorphisms (SNPs) with ~30–70% of enzyme activity, and three SNPs that completely lacked activity altogether. The Endo H assay corroborated these results. Conclusions: Loss of enzyme activity of TYR variants was completely in agreement with ER retention across all variants examined. The results of the assay clearly established that determination of the biological activity of identified variants in patients with OCA is essential to correlate the identified suspect genotype with the obvious phenotype of the disease. Abstract : What's already known about this topic? Oculocutaneous albinism (OCA) is a group of autosomal recessive disorders resulting from congenital hypopigmentation of ocular and cutaneous tissues. Defects in the tyrosinase gene ( TYR ) are a major cause of OCA in many countries. Incidentally, OCA is a major cause of childhood blindness in India. Limited experimental evidence suggests that retention of TYR in the endoplasmic reticulum (ER) is responsible for OCA1 pathogenesis. What does this study add? This study reveals that ER retention of tyrosinase variant proteins is the principal cause of loss of enzyme activity. The study clearly demonstrates that a functional assay of suspect TYR variants is essential to correlate genotype to phenotype in patients with OCA. TYR single‐nucleotide polymorphisms listed in dbSNP, specifically with low or no recorded frequency, could potentially be mutant alleles identified in phenotypically normal heterozygous individuals. What is the translational message? Using OCA1 as a model disease, it is proposed that identification of rare or unique genetic variants in the causal gene of an inherited disease must be complemented with functional studies to implicate the suspect variants with the disease unequivocally. For genetic diseases, correct determination of causal mutations has far‐reaching implications for genetic counselling and/or prenatal diagnosis, as appropriate.